Wide field spectral imaging with shifted excitation raman difference spectroscopy using the nod and shuffle technique - Korinth, Florian; Schmaelzlin, Elmar; Stiebing, Clara; Urrutia, Tanya; Micheva, Genoveva; Sandin, Christer; Mueller, Andre; Maiwald, Martin; Sumpf, Bernd; Krafft, Christoph; Traenkle, Guenther; Roth, Martin M.; et al. (Sensors, 2020)
Wide field Raman imaging using the integral field spectroscopy approach was used as a fast, one shot imaging method for the simultaneous collection of all spectra composing a Raman image. For the suppression of autofluorescence and background signals such as room light, shifted excitation Raman difference spectroscopy (SERDS) was applied to remove background artifacts in Raman spectra. To reduce acquisition times in wide field SERDS imaging, we adapted the nod and shuffle technique from astrophysics and implemented it into a wide field SERDS imaging setup. In our adapted version, the nod corresponds to the change in excitation wavelength, whereas the shuffle corresponds to the shifting of charges up and down on a Charge-Coupled Device (CCD) chip synchronous to the change in excitation wavelength. We coupled this improved wide field SERDS imaging setup to diode lasers with 784.4/785.5 and 457.7/458.9 nm excitation and applied it to samples such as paracetamol and aspirin tablets, polystyrene and polymethyl methacrylate beads, as well as pork meat using multiple accumulations with acquisition times in the range of 50 to 200 ms. The results tackle two main challenges of SERDS imaging: gradual photobleaching changes the autofluorescence background, and multiple readouts of CCD detector prolong the acquisition time.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Autofluorescence; Background suppression; Diode lasers; Integral field spectroscopy; Nod and shuffle; Photobleaching; Raman spectroscopy; SERDS; Wide field imaging